A single vaccination of nucleoside-modified Rabies mRNA vaccine induces prolonged highly protective immune responses in mice - Bai, Shimeng; Yang, Tianhan; Zhu, Cuisong; Feng, Meiqi; Zhang, Li; Zhang, Ziling; Wang, Xiang; Yu, Rui; Pan, Xinghao; Zhao, Chen; Xu, Jianqing; Zhang, Xiaoyan (Frontiers in Immunology, 2023)
Rabies is a lethal zoonotic disease that kills approximately 60,000 people each year. Although inactivated rabies vaccines are available, multiple-dose regimens are recommended for pre-exposure prophylaxis or post-exposure prophylaxis, which cuts down the cost- and time-effectiveness, especially in low- and middle-income countries. In this study, we developed a nucleoside-modified Rabies mRNA-lipid nanoparticle vaccine (RABV-G mRNA-LNP) encoding the codon-optimized glycoprotein and compared its immunogenicity with a commercially available inactivated vaccine. Our results first showed that, when evaluated in mice, a single vaccination of RABV-G mRNA with a moderate or high dose induces more potent humoral and T-cell immune responses than that elicited by three inoculations of the inactivated vaccine. Importantly, mice receiving a single immunization of RABV-G mRNA, even at low doses, showed full protection against the lethal rabies challenge. We further demonstrated that the humoral immune response induced by single RABV-G mRNA vaccination in mice could last for at least 25 weeks, while a two-dose strategy could extend the duration of the highly protective response to one year or even longer. In contrast, the three-dose regimen of inactivated vaccine failed to do so. Together, these data confirmed that it is worth developing a single-dose nucleoside-modified Rabies mRNA-LNP vaccine, which could confer much prolonged and more effective protection.